"I wanna talk about Antonin Artaud" - de Peretti, Cristina (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper goes over the multifaceted work of Artaud, paying special attention, from Derrida’s readings, to some of the most relevant topics of the Artaudian corpus: the Expropriation and Reappropriation of the Self, the Theatre of Cruelty and the Metaphysics of Flesh, the new Language and the Glossolalias, the Pictograms and the sorts, the subjectile and the Work without Work.